The role of transplantation in Hodgkin lymphoma - Maranzano, Michael; Mead, Monica (Frontiers in Oncology, 2023)
Despite the success of frontline anthracycline-based chemotherapy for classical Hodgkin Lymphoma (cHL), approximately 15% of patients do not achieve an adequate response and require further therapy. For transplant-eligible patients, additional treatment followed by high-dose chemotherapy and autologous hematopoietic stem cell transplantation (autoHCT) provides a durable response in 50% of patients. The most refractory patients, including those requiring multiple lines of therapy to achieve a response or those relapsing after an autoHCT, may achieve long-term survival with allogeneic hematopoietic stem cell transplant (alloHCT). Contemporary salvage regimens used as a bridge to transplant have expanded to include not only non-cross resistant chemotherapy, but also brentuximab vedotin (BV) and checkpoint inhibitors (CPI). As the management of relapsed/refractory (R/R) cHL evolves with the introduction of novel agents, so too does the role of transplantation. The paradigm of chemosensitivity as a predictor for autoHCT efficacy is being challenged by favorable post-autoHCT outcomes in heavily pre-treated CPI-exposed patients. Contemporary supportive care measures, validated comorbidity assessments, and an increased donor pool with haploidentical donors have broadened the application of transplantation to an increasingly older and diverse patient population. Despite the introduction of increasingly effective treatment options for R/R cHL, transplantation continues to play an important role in the management of these patients. In this review, we explore the impact of salvage therapy on autoHCT, conditioning regimens, maintenance therapy and the diminishing role of alloHCT for patients with cHL.